Nikolai Nikolaevich and Camouflage : two novels - Aleshkovskiĭ, I͡Uz (Russian library (Columbia University. Press), 2019)
Yuz Aleshkovsky turned Soviet reality into mad monologues whose unhinged speakers revealed everyday and cosmic truths. These two novels display his vivid imagination and unmistakable voice.